List composition effect on cognate and non-cognate word acquisition in children - Comesaña, Montserrat (2019)
Previous studies on second language (L2) vocabulary acquisition with children showed that the use of a picture learning method favours the creation of direct links between the semantic system and new lexical representations at early stages of L2 acquisition (Comesaña et al., 2009). However, recent studies found that this influence seems to vary according to the cognate status of the words being learned (Comesaña et al., 2012), raising the question of how the type of words involved can modulate the lexical-semantic connections between the words of both languages in the bilingual memory. The main goal of the present study was to explore list composition effects in the establishment of L2 word-to-concept connections in Portuguese children by using a picture-based method. Results showed no influence of list composition in the establishment of L2 lexical-semantic connections when cognates have to be learned. Findings are discussed in light of relevant models of bilingual memory.